2007
DOI: 10.1093/ecam/nen003
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of a Traditional Herbal Medicine, Hochu-ekki-to in the Long‐Term Management of Kikyo (Delicate Constitution) Patients with Atopic Dermatitis: A 6‐Month, Multicenter, Double‐Blind, Randomized, Placebo‐Controlled Study

Abstract: Hochu-ekki-to is a traditional herbal (Kampo) medicine that has been shown to be effective for patients with Kikyo (delicate, easily fatigable, or hypersensitive) constitution. Previous case reports have suggested that this herbal drug was effective for a certain subgroup of patients with atopic dermatitis (AD). We aimed to evaluate the efficacy and safety of Hochu-ekki-to in the long-term management of Kikyo patients with AD. In this multicenter, double blind, randomized, placebo-controlled study, 91 Kikyo pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
69
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 33 publications
(36 reference statements)
0
69
0
1
Order By: Relevance
“…This manufacturersponsored trial by Kobayashi and colleagues 437 compared a herbal tea, Hochu-ekki-to (containing 10 species of medicinal plants), against placebo for 24 weeks. Ninety-one participants with eczema according to the Japanese Dermatological Association criteria 26 and a delicate (Kikyo) constitution took the interventions twice a week for 24 weeks.…”
Section: Studiesmentioning
confidence: 99%
“…This manufacturersponsored trial by Kobayashi and colleagues 437 compared a herbal tea, Hochu-ekki-to (containing 10 species of medicinal plants), against placebo for 24 weeks. Ninety-one participants with eczema according to the Japanese Dermatological Association criteria 26 and a delicate (Kikyo) constitution took the interventions twice a week for 24 weeks.…”
Section: Studiesmentioning
confidence: 99%
“…33) In a clinical study, concomitant hochuekkito significantly reduced the dose of topical corticosteroids and tacrolimus needed without aggravating dermatitis. 34) orengedokuto and yokukansan are used for eczema exacerbated by physical and emotional stress. Atopic dermatitis can also be exacerbated by physical irritation and social stress.…”
Section: )mentioning
confidence: 99%
“…The study results demonstrated that Hochu-ekki-to significantly reduced the required dose of topical steroids and/or tacrolimus without further aggravating the underlying condition. 26 Due to the contradictory results of previous studies and the limited number of trials assessing the effects of herbal medicine in patients with AD, this study of TJ-15 plus TJ-17 was carried out based on pattern identification, a basic principle of TCM/TKM. Huanglian Jiedu san or TJ-15, an herbal compound, has been reported to be effective in treating noninfectious chronic inflammatory diseases including cerebral and cardiovascular diseases.…”
Section: Tj-15 Tj-17 For Ad and Pattern Identificationmentioning
confidence: 99%